Improving Vocabulary Mastery Using Intralingual Subtitle and Vocabulary Self-Collection Strategy - Utomo, Dias (JET ADI BUANA, 2020)
As one of the language components, vocabulary is an essential factor to master language skills. However, learning vocabulary is assumed to be a boring activity that the students are not interested in. This research aims at improving students’ vocabulary mastery using intralingual subtitle and vocabulary self-collection strategy. A classroom action research was carried out to solve the seventh (7th) graders’ problems regarding vocabulary mastery. The subjects of the study were 35 students of seventh grade at one of the junior high schools in Malang. The instruments used in this study were an interview guide for the English teacher, observation notes, questionnaire, and vocabulary tests. The researcher set the criteria of success 75% of the students achieved a score equal or higher than 75 in the vocabulary test and 75% of the students showed positive responses toward the implementation of the strategy. The result of the study showed that (1) 83% of the students or 29 out of 35 students achieved score equal or higher than 75, indicating that the use of intralingual subtitle and vocabulary self-collection strategy improved students’ vocabulary mastery, (2) there were 5 (five) major steps in implementing intralingual subtitle and vocabulary self-collection strategy to improve students’ vocabulary mastery, (3) 90% of the students showed the positive responses to the implementation of the strategy. Keywords: teaching vocabulary, intralingual subtitle, vocabulary self-collection strategy, junior high school